Peran Pemerintah Kabupaten Ponorogo Dalam Pelembagaan Kesenian Reyog - Candra Sari, Alrisa Ayu; S, Sutomo; Makmur, M. Hadi (e-Sospol, 2016)
Abstract This study aimed to describe the role of Local Government of Ponorogo Regency in institutionalization of Reyog. Reyog is a local culture that becomes a national icon. However, in its development, Reyog has not been utilized well as well as decreases in quantity. This type of approach was qualitative, symbolic interaction mainstream, and descriptive purpose. The sources of data used were primary data obtained from interview and observation of passive participation and supported by secondary data from documentation and library study. Technique of data validity test (triangulation) used method and data sources. Meanwhile, the techniques used determining the informants were purposive and snowball samplings. Data analysis was carried out by interactive model. The research showed that the facilitation of Reyog activities had been programmed in routines and have sustained from 1995 to present in Ponorogo making Reyog group activities in following festival sustainably and setting tourism image of Reyog in Ponorogo massively.